Relationships between grain quality and leaf carbon and nitrogen status in high-quality hybrid rice across different sowing dates and nitrogen management - Xie, Jiaxin; Liu, Mengjie; Xiao, Zhengwu; Li, Xing; Cao, Fangbo; Chen, Jiana; Huang, Min; Ali, Izhar; Iqbal, Anas; Wahab, Abdul; Guo, Shuchun (Frontiers in Agronomy, 2025)
IntroductionThere is a knowledge gap regarding the effects of sowing date and nitrogen (N) management on the grain quality, as well as the relationship between grain quality and leaf carbon (C) and N status in high-quality hybrid rice.MethodsThis study aimed to compare the grain quality of high-quality hybrid rice and evaluate the relationships between grain quality and leaf C and N content, as well as the C/N ratio, across different sowing dates and N management strategies in 2022 and 2023. Two sowing dates were employed for each year, and for each sowing date and year, rice cultivars were subjected to two N rates and three N split-application ratios.Results and discussionResults showed that delaying the sowing date increased head rice rate, amylose content, setback viscosity and leaf N content at the maturity stage while decreasing protein content, peak and breakdown viscosity, and leaf C/N ratio. Increasing N rate and delaying N application boosted head rice rate, amylose and protein content, setback viscosity, and leaf N content at both the heading and maturity stages but reduced peak and breakdown viscosity, and leaf C/N ratio. When leaf N content was below 2.92% and 1.44% at the heading and maturity stages, and the leaf C/N ratio was above 14.9 and 29.5, respectively, it enhanced the eating quality but did not improve milling and nutritional quality. These findings suggest that delaying the sowing date can improve milling quality but deteriorate the eating and nutritional quality of high-quality hybrid rice. Increasing N rate and delaying N application are beneficial to milling and nutritional quality but are unfavorable for improving eating quality. The leaf N content and C/N ratio at the heading and maturity stages are effective indicators for diagnosing grain quality.